Internal Control Systems And Village Fund Fraud Prevention: Does Community Participation Matter? - Abellinda Preacyllia; RR Karlina Aprilia Kusumadewi (Politeknik Ganesha Medan, 2026)
This reserach aims to investigate the effect of the Internal Control System (ICS) on the fraud prevention in Wonogiri Regency, while also exploring the moderating role of community involvement. This study employed a quantitative approach, conducting a survey among 251 village officials in Wonogiri Regency. A total of 152 participants were included in the study, selected through stratified random sampling. Data analysis was conducted using Structural Equation Modeling Partial Least Squares (SEM-PLS). The findings show that internal control system has a positive effect on fraud prevention. Furthemore, community participation was found to strengthen the effectiveness of the internal control system in preventing fraud, as it functions as an external supervisory mechanism that monitors all stage of village fund management. These findings emphasize the importance of combining formal internal controls with social oversight by the community to create layered supervision that reduces opportunities for fraud. The study provides implications for village governments to continuously strengthen the ICS and enhance community involvement in managing village funds, thereby ensuring transparency, accountability, and compliance. Keywords: Community Participation; Fraud Prevention; Internal Control System.